2022
DOI: 10.3389/fonc.2021.759952
|View full text |Cite
|
Sign up to set email alerts
|

A Novel IGLC2 Gene Linked With Prognosis of Triple-Negative Breast Cancer

Abstract: BackgroundImmunoglobulin-related genes are associated with the favorable prognosis of triple-negative breast cancer (TNBC) patients. We aimed to analyze the function and prognostic value of immunoglobulin lambda constant 2 (IGLC2) in TNBC patients.MethodsWe knocked down the gene expression of IGLC2 (IGLC2-KD) in MDA-MB-231 cells to evaluate the proliferation, migration, and invasion of tumors via 3-(4,5-Dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay, wound healing, and transwell cell migration ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…IGLC2 has a similar expression and functional pattern to LINC01871 in our study ( Figure 8 ). Chang et al (2021 ) found in a study of triple-negative breast cancer (TNBC) cohort that a high expression of IGLC2 was related to a favorable prognosis for TNBC patients, which is consistent with our results. In addition, IGLC2 is linked with the proliferation, migration, and invasion of MDA-MB-231 cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…IGLC2 has a similar expression and functional pattern to LINC01871 in our study ( Figure 8 ). Chang et al (2021 ) found in a study of triple-negative breast cancer (TNBC) cohort that a high expression of IGLC2 was related to a favorable prognosis for TNBC patients, which is consistent with our results. In addition, IGLC2 is linked with the proliferation, migration, and invasion of MDA-MB-231 cells.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, IGLC2 is linked with the proliferation, migration, and invasion of MDA-MB-231 cells. Pathway enrichment analysis showed that IGLC2 is related to the extracellular matrix–receptor interaction ( Chang et al, 2021 ). All these features make IGLC2 have the potential to be a biomarker to predict prognosis, even for identifying breast cancer patients who can benefit the most from immune checkpoint blockade treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We also performed differential expression gene analysis for Tumor_edge_3 region based on the annotation results of PAST on BCS2, and identified the five most significant differential expression genes (DEGs) including IGHG3, IGKC, IGLC2, IGHG4 and IGHG1 with adjusted p -values of 1.11e-83, 1.86e-78, 9.18e-74, 9.18e-74 and 1.66e-69, respectively. According to previous literature, the linkage of IGHG1/3/4 provides information for prognosis of diseases like autoimmunity and malignancy 41 , IGKC , serving as a robust immune marker, could predict metastasis-free survival and response to chemotherapy 42 , and IGLC2 was proved to be a significant prognostic biomarker for triple-negative breast cancer patients 43 . The gene ontology (GO) enrichment for the top 10 DEGs of Tumor_edge_3 also significantly revealed lots of biological immune processes (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, YWHAH might be associated with various cancers, and its polymorphisms are implicated to be genetically associated with schizophrenia. 76 In humans, Iglc2 or (Ig lambda-2 chain C region) gene has been recently linked to the prognosis of triple-negative breast cancer 77 and its deposition in AL-amyloid lesions is linked to a new disease entity of AL amyloidosis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%